2018
DOI: 10.1002/jbm.b.34095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the durability of UHMWPE biomaterials used for articulating surfaces of joint arthroplasty using delamination tests

Abstract: Ultra-high molecular weight polyethylene (UHMWPE) is the most popular material used for the articulating surface of joint replacements. Delamination is a common fatigue-related failure mode in UHMWPE components; however, the relationship between delamination resistance and fatigue crack growth has not been reported. Here, the delamination resistance of contemporary UHMWPE materials, including highly cross-linked UHMWPE (HXLPE), vitamin E blended UHMWPE (VEPE), and vitamin E blended HXLPE (VEXLPE), was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
5
12
0
Order By: Relevance
“…It has been reported that the fatigue properties obtained by fatigue crack growth testing do not necessarily coincide with delamination resistance (Sakoda et al, 2019). Therefore, in this study, delamination tests—which have been reported to be consistent with in vivo behavior—were also conducted (Sakoda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that the fatigue properties obtained by fatigue crack growth testing do not necessarily coincide with delamination resistance (Sakoda et al, 2019). Therefore, in this study, delamination tests—which have been reported to be consistent with in vivo behavior—were also conducted (Sakoda et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the fatigue properties obtained by fatigue crack growth testing do not necessarily coincide with delamination resistance (Sakoda et al, 2019). Therefore, in this study, delamination tests—which have been reported to be consistent with in vivo behavior—were also conducted (Sakoda et al, 2019). Virgin used in this study was equivalent to ethylene gas‐sterilized UHMWPE, which has been reported to experience no delamination in vivo (Greulich, Roy, & Whiteside, 2012; MacDonald, Hanzlik, Sharkey, Parvizi, & Kurtz, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations